Pengaruh Kepuasan Kerja Dan Motivasi Terhadap Komitmen Karyawan Pada PT Glorienta Panca Henna - Bintang Setyo Aguindra; Fiko Farlis (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research is a survey research on students at Dharma Andalas University. This research is entitled "The Influence of Job Satisfaction and Motivation on Employee Commitment at PT Glorienta Panca Henna". The purpose of this research is to determine the influence of job satisfaction and motivation on PT Glorienta Panca Henna. This type of research is quantitative research and the data collection method uses a questionnaire. The population in this study were 57 employees of PT Glorienta Panca Henna. The number of samples taken in this study was 57 respondents. The sampling technique was Saturated Sampling. Based on the results of the research and data analysis using SPSS software version 25, it shows that: (1) Job Satisfaction has a positive and significant effect on employee commitment at PT Glorienta Panca Henna, (2) Motivation has a positive and significant effect on employee commitment at PT Glorienta Panca Henna, (3) Job satisfaction and motivation have a positive and significant effect on employee commitment at PT Glorienta Panca Henna.